Turtles of Kankai (Mai) river and their ethno-medicinal uses - Kharel, Milan; Chhetry, Damodar Thapa (Nepalese Journal of Biosciences, 2013)
This paper deals with 67 specimens belonging to eight different species out of which 4 species were hard-shelled turtles such as Indotestudo elongata, Melanochyles tricarinata, Melanochyles trijuga and Pangshura flaviventer, while rest of 4 species were soft-shelled turtles such as Lissemys punctata, Aspideretes hurum, Aspideretes gangeticus and Chitra indica. Among all, Lissemys punctata was recorded as widely distributed and most abundant species. Ethno-medicinal uses of turtle by Satar, an indigenous ethnic community of southern Jhapa for human and domestic animals have been documented. Most of the diseases are treated by the use of turtle shell of Lissemys punctata. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7500 Nepalese Journal of Biosciences 2 : 126-133 (2012)